Fine structure of the human galactokinase GALK1 gene. - Bergsma, D J; Ai, Y; Skach, W R; Nesburn, K; Anoia, E; Van Horn, S; Stambolian, D

(untitled) (Genome Research, 1996)
Defects in the human GALK1 gene result in galactokinase deficiency and cataract formation. We have isolated this gene and established its structural organization. The gene contains 8 exons and spans approximately 7.3 kb of genomic DNA. The GALK1 promoter was localized and found to have many features in common with other housekeeping genes, including high GC content, several copies of the binding site for the Sp1 transcription factor, and the absence of TATA-box and CCAAT-box motifs typically present in eukaryotic Pol II promoters. Analysis by 5'-RACE PCR indicates that the GALK1 mRNA is heterogeneous at the 5' terminus, with transcription sites occurring at many locations between 21 and 61 bp upstream of the ATG start site of the coding region. In vitro translation experiments of the GALK1 cDNA indicate that the protein is cytosolic and not associated with the endoplasmic reticulum membrane.